Fundamental Approach to University Education and Training of IT Professionals - A. V. Zamyatin; A. I. Chuchalin (Высшее образование в России)
The paper is devoted to education and training of professionals in the IT field in classical universities in the context of the implementation of the Federal Project “Human Resources for the Digital Economy” of the National Program “Digital Economy of the Russian Federation”. The general approach, goals and content of fundamental education and specialized training of Bachelors, Masters and PhD-holders to complex, innovative and research activities have been determined. The structure of Bachelor, Master and PhD programs of the Institute of Applied Mathematics and Computer Science of Tomsk State University modernized on the basis of the above approach, is presented. The paper pays special attention to the training of T-Shaped specialists in IT in classical universities, dwells on the fundamental education of IT specialists. The results of the coordination of programs with employers and students are given.